DEMAM KOREA DAN IMPERIALISME BUDAYA: Kajian booming tayangan Korea terhadap perubahan perilaku di masyarakat - Kartinawati, Erwin (JURNAL KOMUNITAS, 2014)
Korean wave hits many parts in the world. This country is no exception. Not need long time, Indonesian media content also raises many imitation products are said to be mashed with a term inspired show of Korea. Popping electronic sinema with theme, storyline, to property are similar to Korean production. The entertainment industry is also talkative homeland to bring similar icons such as the formation of a boy band or girl band. Korean dramas are able to be one booster television ratings. Loading event with consideration of market appetite has become one of the important things for the continuation of the mass media industry. But the boom shows other domestic product can influence and change behavior of society as well as a shift in values and norms. Incessant media show make people become more permissive to a previously taboo thing. Some of people don’t realize that it can be as a new imperialism, especially in culture.